Sensor de inclinação baseado em FBG - Mok, Roberto Wu (2019)
In this work, the development of an optical temperature-independent tilt sensor based on fiber Bragg granting technology (FBG) is presented. The proposed sensor has a modular topology, in which each module is composed of a pair of FBGs which is fixed to the opposing faces of a metal beam in which a known mass is attached to the free end. When a slope is applied, the beam will be curved due to the action of the gravitational force acting on the mass, which results in an elongation of the pair of FBGs in opposite directions, resulting in a relative displacement of the wavelength difference of the FBGs pair. The FBG sensor pair is attached to supports to increase the sensitivity of mechanical deformation. Since the measurements are encoded in the wavelength, the proposed sensor does not suffer from the optical intensity fluctuations that occur in the light sources. The final prototype was calibrated and bench-tested in the range of -40◦ to +40◦ inclination and an accuracy of ±0, 46◦ , resolution of ±0, 25◦ , and an excellent linearity. In addition, the thermal stability achieved by the proposed sensor was 0, 64◦ in the temperature range of 25 ◦C to 50 ◦C. Finally, the work presented becomes an option to replace the conventional equipment that is currently used in the industry.